Diversidade microbiana e de teores de metais pesados em solos e nas águas superficiais ao longo do rio curu. - Anjos, David Correia dos (2015)
This study aimed to survey the land and the waters surrounding the Curu River with respect to the content of heavy metals and microbial community, besides evaluating the effects of heavy metals on the microbial community of soil. Soil samples were collected from the layers of 0-5 cm and 5-30 cm and river water at 22 sites, close to areas possibly contaminated by heavy metals. The samples were analyzed for granulometry, pH, electrical conductivity (EC), organic matter (OM) on the ground. The water was analyzed temperature, electrical conductivity (EC), saline (SAL), total dissolved solids (TDS), pH, turbidity and the amount of dissolved oxygen (LDO). The heavy metals Arsenic (As), cadmium (Cd), cobalt (Co), chromium (Cr), copper (Cu), molybdenum (Mo), nickel (Ni), lead (Pb) and selenium (Se) were determined in water samples and soil. The responses of microbial structures to the different soil uses were evaluated using the PLFA technique. Canonical correlation was used to verify the possible relations between groups of variables (water physical and chemical characteristics, soil physical and chemical characteristics, heavy metals and soil microbiological attributes). The characteristics EC, SAL, TDS, turbidity and LDO water showed at some sites of the river over the standards by CONAMA resolution n.o 357/2005. Faced with heavy metals analyzed in the study, Se it is the only heavy metal found over concentrations at the limit by the Ministry of Health under administrative rule n.o 518/2004 for the potability of water. The physical and chemical characteristics (pH and LDO water) contributed to explain the concentrations of heavy metals Co, Cu and Ni in the water. The soil physical and chemical characteristics (clay, OM, silt, pH and sand) contributed to explain the contents of heavy metals in this soil. However, the behavior of the microbiological attributes cannot be explained by the heavy metals in this soil. According to the national standards of the Environmental Company of São Paulo State (CETESB), some sites in the studied area are contaminated by heavy metals Ni, Pb and Se.